VBP15, a novel anti‐inflammatory and membrane‐stabilizer, improves muscular dystrophy without side effects. Issue 10 (9th September 2013) - Heier, Christopher R.; Damsker, Jesse M.; Yu, Qing; Dillingham, Blythe C.; Huynh, Tony; Van der Meulen, Jack H.; Sali, Arpana; Miller, Brittany K.; Phadke, Aditi; Scheffer, Luana; Quinn, James; Tatem, Kathleen; et al.
<x xml:space="preserve">Abstract</x> Absence of dystrophin makes skeletal muscle more susceptible to injury, resulting in breaches of the plasma membrane and chronic inflammation in Duchenne muscular dystrophy (DMD). Current management by glucocorticoids has unclear molecular benefits and harsh side effects. It is uncertain whether therapies that avoid hormonal stunting of growth and development, and/or immunosuppression, would be more or less beneficial. Here, we discover an oral drug with mechanisms that provide efficacy through anti‐inflammatory signaling and membrane‐stabilizing pathways, independent of hormonal or immunosuppressive effects. We find VBP15 protects and promotes efficient repair of skeletal muscle cells upon laser injury, in opposition to prednisolone. Potent inhibition of NF‐κB is mediated through protein interactions of the glucocorticoid receptor, however VBP15 shows significantly reduced hormonal receptor transcriptional activity. The translation of these drug mechanisms into DMD model mice improves muscle strength, live‐imaging and pathology through both preventive and post‐onset intervention regimens. These data demonstrate successful improvement of dystrophy independent of hormonal, growth, or immunosuppressive effects, indicating VBP15 merits clinical investigation for DMD and would benefit other chronic inflammatory diseases.